2011
DOI: 10.1155/2011/427473
|View full text |Cite
|
Sign up to set email alerts
|

Surface TLR2 and TLR4 Expression on Mature Rat Mast Cells Can Be Affected by Some Bacterial Components and Proinflammatory Cytokines

Abstract: The aim of our study was to determine whether some bacterial components as well as some proinflammatory cytokines can affect surface mast cell levels. By the use of flow cytometry technique, we documented that freshly isolated mature rat peritoneal mast cells do express surface TLR2 and TLR4 protein, but not CD14 molecules, and respond to stimulation with TLR2 and TLR4 ligands by cysteinyl leukotriene generation. The level of TLR2 protein is modulated by PGN and CCL5 treatment, but not by LPS, LAM, TNF, or IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 57 publications
2
33
0
1
Order By: Relevance
“…Only TLR2, TLR3, and TLR4 proteins were found in mast cells from isolated human nasal polyps [22], murine peritoneal cavity [38], and FSMC [30]. Our previous studies have shown that freshly isolated rat peritoneal mast cells express both surface TLR2 and TLR4 molecules [20, 39], as well as TLR3 and TLR7 surface proteins [40, 41]. In this study we evaluated the expression of TLR receptors in native fully mature rat mast cells freshly isolated from the peritoneal cavity, that is connective tissue type mast cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only TLR2, TLR3, and TLR4 proteins were found in mast cells from isolated human nasal polyps [22], murine peritoneal cavity [38], and FSMC [30]. Our previous studies have shown that freshly isolated rat peritoneal mast cells express both surface TLR2 and TLR4 molecules [20, 39], as well as TLR3 and TLR7 surface proteins [40, 41]. In this study we evaluated the expression of TLR receptors in native fully mature rat mast cells freshly isolated from the peritoneal cavity, that is connective tissue type mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells were prepared with purity > 98%, as determined by metachromatic staining with toluidine blue. The viability of mast cells was over 98%, as estimated by trypan blue exclusion assay [20]. …”
Section: Methodsmentioning
confidence: 99%
“…The Toll-like receptors (TLRs), a major class of pathogen-associated molecular patterns, are molecules associated with groups of pathogens recognized by innate immune system cells. Ligand engagement of mast cell surface TLR2/TLR4 triggers cytokine release which recruits immune cells to the sites of injury; microglia recruitment depends on signaling pathways involving TLR2/ TLR4 [35]. Mast cell activation up-regulates chemokine expression, including CCL5/RANTES; the latter are capable of inducing a pro-inflammatory response in microglia.…”
Section: Glia and Mast Cells: The Dynamic Duo Of Neuroinflammationmentioning
confidence: 99%
“…In our experiments we mimicked acute inflammatory conditions by adding substance P, an inflammatory neuropeptide; PGN, the infective component of gram-positive bacteria Staphylococcus aureus; and anti-rat DNP IgE followed by DNP-HSA as an allergic stimulus to compare potential aging-associated differences in mast cell activation in response to acute inflammation. Substance P, peptidoglycan, and IgE are associated with inflammatory, infective, and allergic reactions and are also known to activate mast cells (6,10,11,31,32,34,47,50,58,74). Compound 48/80, a chemical activator of mast cells (30,64,73), was used as a positive control, and physiological salt solution (PSS) was used as a negative control (sham) for these studies.…”
Section: Animals and Surgerymentioning
confidence: 99%